1985
DOI: 10.1001/archotol.1985.00800140038006
|View full text |Cite
|
Sign up to set email alerts
|

Sensorineural Hearing Loss in Experimental Purulent Otitis Media due to Streptococcus pneumoniae

Abstract: \s=b\Sensorineural hearing loss (SNHL) has been described clinically following chronic otitis media with effusion, but to the best of our knowledge, no studies have demonstrated SNHL in an animal model of otitis media. Using the chinchilla model of pneumococcal otitis media, significant SNHL was demonstrated after purulent otitis media, especially at higher frequencies. Animals with otitis media received penicillin G procaine treatment for five days after otitis media with effusion (OME) was first documented; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(26 citation statements)
references
References 12 publications
3
23
0
Order By: Relevance
“…SNHL was observed in high-frequency areas (14,16,20 and 31.5 kHz) thus being in agreement with one previous report [9]. We found that the mean of the threshold changes was approximately 10 dB at 31.5 kHz, 5 dB at 20 kHz and below 5 dB at 16 and 14 kHz.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…SNHL was observed in high-frequency areas (14,16,20 and 31.5 kHz) thus being in agreement with one previous report [9]. We found that the mean of the threshold changes was approximately 10 dB at 31.5 kHz, 5 dB at 20 kHz and below 5 dB at 16 and 14 kHz.…”
Section: Discussionsupporting
confidence: 93%
“…Pneumococci produce various toxic proteins such as pneumolysin, autolysin, neuraminidase, hyaluronidase and pneumococcal surface protein A [8]. SNHL following inoculating viable pneumococci has been reported [9]. Recently, the importance of their cell wall component has been emphasized to cause the inflammatory reaction [10].…”
Section: Introductionmentioning
confidence: 99%
“…the basal part of the cochlea. These results appear compatible with previous reports concerning the penetration of ototoxic substances through the RWM [22][23][24]. Together with the results of morphological examination, two possible interpretations for cochlear dysfunction by IL-8 may be suggested: one indirect, that such substances as lysosomal enzymes, ROS and NO, suspected of being injurious to cochlear tissues, were released from neutrophils attracted by IL-8 into the middle ear cavity to pass through the RWM and/or from neutrophils attracted by IL-8 in cochlear fluids and spread toward the upper cochlear turns with decreasing concentration; the other is a direct but unknown effect of IL-8 to influence homoeostasis in the cochlea.…”
Section: Discussionsupporting
confidence: 93%
“…It is hypothesised that in CSOM toxins enter through semipermeable round window membrane causing damage to organ of Corti Paparella, Morizona. 3,4 Chronic suppurative otitis media is fairly common disease in our country especially in rural community. 5 WHO in 2004 mentioned, the worldwide prevalence of chronic suppurative otitis media is 65-330 million people and 39-200 million (60%) suffer from clinically significant hearing impairment.…”
Section: Introductionmentioning
confidence: 99%